Integration of Trypanosoma cruzi kDNA minicircle sequence in the host genome may be associated with autoimmune serum factors in chagas disease patients - Barbosa, Augusto Mello Simões (1999)
ABSTRACT: Integration of kDNA sequences within the genome of the host cell shown by PCR amplification with primers to the conserved Trypanosoma cruzi kDNA minicircle sequence was confirmed by Southern hybridization with specific probes. The cells containing the integrated kDNA sequences were then perpetuated as transfected macrophage subclonal lines. The kDNA transfected macrophages expressed membrane antigens that were recognized by antibodies in a panel of sera from ten patients with chronic Chagas disease. These antigens barely expressed in the membrane of uninfected, control macrophage clonal lines were recognized neither by factors in the control, non-chagasic subjects nor in the chagasic sera. This finding suggests the presence of an autoimmune antibody in the chagasic sera that recognizes auto-antigens in the membrane of T. cruzi kDNA transfected macrophage subclonal lines.